Implementation of Simple Additive Weighting For Scholarship Admission Selection - Joko Kuswanto; M Nang Al Kodri; Trisilia Devana; Leni Pebriantika; Sulia Ningsih (TIERS Information Technology Journal, 2023)
Various types of scholarships are given to students who have achievements both academic and non-academic achievements. Conditions that often occur in the process of awarding scholarships, the assessment is not always decided based on definite considerations and predetermined criteria. Therefore, a decision support system is needed that can assist the scholarship selection team in making effective and efficient decisions. The decision support system to be built applies the Simple Additive Weighting (SAW) method with criteria such as IPS, GPA, Parents' Income, Number of Dependents of parents and Achievement. With the new system, it is expected to help the selection team related to managing applicant data, selection and proposal of scholarship recipients can be done more easily and quickly. After calculation, the highest score of 90.5 was obtained on behalf of Candra K which deserves to be a priority and recommended in receiving scholarships.